6s-2=8s

Simple and best practice solution for 6s-2=8s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6s-2=8s equation:


Simplifying
6s + -2 = 8s

Reorder the terms:
-2 + 6s = 8s

Solving
-2 + 6s = 8s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-8s' to each side of the equation.
-2 + 6s + -8s = 8s + -8s

Combine like terms: 6s + -8s = -2s
-2 + -2s = 8s + -8s

Combine like terms: 8s + -8s = 0
-2 + -2s = 0

Add '2' to each side of the equation.
-2 + 2 + -2s = 0 + 2

Combine like terms: -2 + 2 = 0
0 + -2s = 0 + 2
-2s = 0 + 2

Combine like terms: 0 + 2 = 2
-2s = 2

Divide each side by '-2'.
s = -1

Simplifying
s = -1

See similar equations:

| 5(x-8)=3(3x-40) | | 4+3(4n+6)-n= | | 9x-6(x-1)=1 | | 6(d-6)=4(d-60)+2d | | -7x+(-7x-30)=36 | | 9mn/4n | | -2x^2+6x+8=12 | | -1=-5-4s | | 18z^3+9z^2-50z-25=0 | | x^2=y^2-20.25 | | 4(-5x+35)-x+7=0 | | 5x/2-8=2x-7/6 | | 2s+7=-5s | | 10a-83=203 | | X=(18+8) | | x=(x)(x) | | 34-2x=80 | | X^2-76+1380=0 | | 258=175-w | | 250=10e | | -2(2q-4)=10q-20 | | 11y+12=45 | | Sin(x)=-0.62 | | 9-7p=8 | | 09-7p=8 | | x+18+3*x=74 | | 8w+2=90 | | 11/h-5=7/5-h | | 68x=y-2875 | | 3x-(3x^2-7x)+8x^2= | | 11p+12=45 | | 2-(13-m)=-(m-19)-6 |

Equations solver categories